Relationships between Cognitive Function and Odor Identification, Balance Capability, and Muscle Strength in Middle-Aged Persons with and without Type 2 Diabetes. (7th October 2021) - Midorikawa, Manabu; Suzuki, Hiroaki; Suzuki, Yasuhiro; Yamauchi, Kazuyoshi; Sato, Hiroyuki; Nemoto, Kiyotaka; Sugano, Yoko; Iwasaki, Hitoshi; Sekiya, Motohiro; Yatoh, Shigeru; Yahagi, Naoya; Hada, Yasushi; et al.
Abstract : Aim . We investigated the relationship between cognitive function and olfactory and physical functions in middle-aged persons with and without type 2 diabetes (T2D) to examine the potential of olfactory and physical functions as biomarkers for early cognitive impairment. Methods . Enrolled were 70 T2D patients (age 40 to <65 y) and 81 age-matched control participants without diabetes. Cognitive function was assessed by the Montreal Cognitive Assessment (MoCA), Trail Making Test parts A and B (TMT-A/-B), Wisconsin Card Sorting Test (WCST), Quick Inventory of Depressive Symptomatology Self-Report (QIDS), and Starkstein Apathy Scale (SAS). Multiple linear regression analyses were performed. Results . Odor identification was an independent determinant shown in the results of the TMT-A in the entire participant group and was independently associated with the MoCA and TMT-B in the T2D group. Balance capability assessed with a stabilometer was independently associated with all cognitive function tests except for QISD and SAS in the entire participant group and the T2D group and was independently associated with TMT-A in the control group. Knee extension strength was independently associated with the SAS in the entire participant group and the T2D group. Conclusions . Odor identification, balance capability, and knee extension strength were potential markers for cognitive decline in middle-aged persons with T2D.